2017
DOI: 10.1111/jdv.14312
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in bullous pemphigoid: a case–control analysis of bullous pemphigoid patients with age‐ and gender‐matched controls

Abstract: Our study has shown that a significant proportion of patients with BP are multimorbid and individually have a higher number of comorbidities compared to matched controls. Disease burden and multimorbidity may well impact the prognosis of patients with BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
0
39
1
1
Order By: Relevance
“…The increased risk for mortality aligns with a recently published case-control study reporting that BP patients are highly fragile and are multimorbid and individually have a greater number of comorbidities relative to matched controls. 19 The disease burden and multimorbidity have a substantial impact on the prognosis of patients with BP.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk for mortality aligns with a recently published case-control study reporting that BP patients are highly fragile and are multimorbid and individually have a greater number of comorbidities relative to matched controls. 19 The disease burden and multimorbidity have a substantial impact on the prognosis of patients with BP.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 In another study concerning BP patients, multi-morbidity was observed in 84% with the highest percentage for arterial hypertension. 22 On the other hand, Jedlickova et al did not find differences in cardiovascular disease incidences among patients with BP and controls. 7 Nevertheless, a certain role in the pathogenesis of BP is attributed to drug consumption, especially agents used to treat hypertension.…”
Section: Association With Cardiovascular Diseasesmentioning
confidence: 92%
“…The fact is that this disease may play an important role in BP patients, especially since major drugs used to treat hypertension such as diuretics, ACE inhibitors or spironolactone can provoke BP. 6,13,[20][21][22] Among other comorbidities, single studies have demonstrated the association of BP with diabetes. [23][24][25] To confirm or reject the abovementioned discrepancies, the aim of this study was to assess the relationship between BP and selected comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…This study of Finnish BP patients reveals a strong association between DH and BP. Neither DH nor CD were analyzed in previous studies of BP comorbidities (Bastuji-Garin et al, 2011;Chen et al, 2011;Jedlickova et al, 2010;Jeon et al, 2018;Kibsgaard et al, 2017;Sim et al, 2017;Teixeira et al, 2014). In a British interview-based study of BP and other autoimmune disorders, neither DH nor CD were among the diseases about which the participants (n ¼ 108) were asked (Taylor et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic conditions are well known to be associated with BP, and psychiatric diseases, psoriasis, hypertension, hematologic malignancies, and diabetes have also been reported as comorbidities of BP (Atzmony et al, 2017;Chen et al, 2011;Kibsgaard et al, 2017;Kridin and Bergman, 2017;Schulze et al, 2015;Sim et al, 2017). DH is associated with type I diabetes, thyroid diseases, and other autoimmune diseases (Bolotin and Petronic-Rosic, 2011a;Collin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%